1999
DOI: 10.1080/08964289909595741
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression and Risk for Postpartum Complications: Role of Prenatal Corticotropin-releasing Hormone and Interleukin-1 Receptor Antagonist

Abstract: The pregnancies of 58 healthy adolescents (ages 13 to 19 years) were followed to examine links between symptoms of depression, corticotropin-releasing hormone (CRH), interleukin-1 beta, (IL-1 beta), and IL-1 receptor antagonist (IL-1ra) as possible predictors of maternal and infant outcomes. Maternal psychological adjustment and medical complications during gestation, labor, delivery, and the postpartum period were monitored. Plasma samples collected during gestation were assayed for CRH, IL-1 beta, and IL-1ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…All five found a significant association between mood and at least one inflammatory marker. Schmeelk et al (1999) studied 58 pregnant adolescents. Blood samples for IL-1β and IL-1ra were drawn between 9 and 21 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All five found a significant association between mood and at least one inflammatory marker. Schmeelk et al (1999) studied 58 pregnant adolescents. Blood samples for IL-1β and IL-1ra were drawn between 9 and 21 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…While we know that the greatest risk factor for postpartum depression is antenatal depression, there is nevertheless some evidence that these may be two separate disorders, as a portion of women develop postpartum depression independent of any depressive symptoms during pregnancy (Wisner et al 2013); they certainly represent different endocrine and inflammatory states. Both the Scrandis et al (2008) and Schmeelk et al (1999) studies used blood draws at multiple time points in an attempt to account for changes across time. In the Scrandis et al study, however, the IL-1β sample was usable in only 4 subjects, blood was drawn many weeks before mood was assessed, inflammatory markers were measured during pregnancy and mood after, and the authors did not attempt a direct correlation between mood and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Geiger et al reported that in neonates who received invasive intensive care, circulating IL-1ra levels were significantly higher than those in the reference group of healthy newborns [18]. Schmeelk et al demonstrated clinical evidence that lower levels of IL-1ra predicted higher rates of maternal complications after childbirth [20].…”
Section: Discussionmentioning
confidence: 98%
“…For example, women who are depressed during pregnancy are at increased risk for anxiety disorders, substance use disorders, tobacco and alcohol use, and poor selfcare (Zuckerman, Amaro, Bauchner, & Cabral, 1989). In addition, these women may experience preeclampsia and other health complications (Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkla, 2000;Schmeelk, Granger, Susman, & Chrousos, 1999). Each of these maternal conditions/behaviors puts the developing fetus at risk for suboptimal outcomes including low birth weight, preterm delivery, and reduced neuromotor activity (Hoffman & Hatch, 2000;Hedegaard, Henriksen, Sabroe, & Secher, 1993;Rini, Dunkel-Schetter, Wadhwa, & Sandman, 1999;Lundy et al, 1999).…”
Section: Consequencesmentioning
confidence: 97%